Immune checkpoint inhibitors targeting PD-1/PD-L1 in the treatment of human lymphomas - Ribatti, Domenico; Cazzato, Gerardo; Tamma, Roberto; Annese, Tiziana; Ingravallo, Giuseppe; Specchia, Giorgina (Frontiers in Oncology, 2024)
Non-Hodgkin lymphomas (NHLs) encompass a diverse group of malignancies arising from B cells, T cells, and natural killer (NK) cells at various stages of differentiation. Conversely, classical Hodgkin lymphomas (cHLs) primarily feature Reed-Sternberg cells (RSCs) amid a background of reactive immune cells. Immunomodulatory pathways, notably the PD-1/PD-L1 axis, play pivotal roles in tumor immune evasion across both NHLs and cHLs. Elevated expression of PD-1 and PD-L1 is observed in a spectrum of lymphomas, influencing prognosis and treatment response. Therapeutically, immune checkpoint inhibitors (ICIs) targeting PD-1/PD-L1 have revolutionized lymphoma management, particularly in relapsed/refractory cases. Nivolumab and pembrolizumab, among others, have demonstrated efficacy in various B-cell lymphomas, with promising outcomes in cHL. Combination strategies incorporating ICIs with conventional chemotherapy or targeted agents show enhanced efficacy and are being explored extensively. In this review we discuss the most important features of the tumor microenvironment of NHLs and cHLs, address the therapeutic approaches with ICIs and try to outline future perspectives.